Miniature all-solid-state metal oxide pH electrode and application thereof
By designing a micro all-solid metal oxide pH electrode, using Ag/AgCl reference electrode and ruthenium iridium titanium metal oxide working electrode, the problems of easy breakage and difficulty in miniaturization of traditional glass electrodes are solved, and higher stability and Convenient pH measurement process.
Patent Information
- Application Number
- CN202411319343.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-22
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional pH composite glass electrodes have problems such as high impedance, easy to break, difficult to miniaturize, and easy leakage and volatility of liquid electrolytes.
A miniature all-solid metal oxide pH electrode was designed, using Ag/AgCl reference electrode and a ruthenium iridium titanium metal oxide working electrode on the Ti sheet substrate, the electrolyte was cured by ultraviolet light and sealed with porous ceramic membrane and epoxy resin. Form a more robust and controllable small electrode.
It achieves higher mechanical strength, wider application scenarios and more convenient measurement processes, avoiding the easy breakage of glass electrodes and leakage and volatility of liquid electrolytes, and does not require a specific transmitter to perform measurements.
Smart Images

Figure HDA0005053374800000011 
Figure HDA0005053374800000012
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro bioreactors, and in particular relates to a micro all-solid-state metal oxide pH electrode and application thereof. Background Art
[0002] Changes in pH play a key role in cell proliferation in fermentation, cell culture, and various other bioreactor systems. Conventional pH electrodes have demonstrated high accuracy in measuring pH and are widely used in a variety of industrial fields, including bioreactor fermentation, long-distance transportation of natural gas, biofuel production, micro-machines, marine research and exploration, and water quality monitoring and pollution control.
[0003] With the invention of various micro bioreactors, the demand for measuring pH changes in them has gradually increased. The traditional pH composite glass electrode is the most widely used sensor for measuring pH value. However, the glass electrode has high impedance and glass material, so it has the disadvantages of being easy to break and difficult to miniaturize. In order to overcome its shortcomings such as being unable to be applied to more measurement scenarios and breaking the leading position and monopoly of mainstream traditional electrodes in the fermentation industry, a micro all-solid-state pH electrode is proposed, which has the characteristics of high stability, easy preparation, controllable size and simple measurement. Summary of the invention
[0004] Based on the shortcomings or deficiencies of the prior art, the present invention provides a miniature all-solid-state metal oxide pH electrode and its application. The technical problem solved by the present invention is that the traditional pH composite glass electrode has the problems of high impedance, easy breakage of glass material, difficulty in miniaturization, etc., and the reference electrode used in it uses liquid electrolyte, which is easy to leak during use and easy to volatilize when stored in the air.
[0005] The technical solution of the present invention is a micro all-solid-state metal oxide pH electrode, which consists of a reference electrode and a working electrode, wherein the reference electrode is an Ag / AgCl reference electrode; the working electrode consists of a Ti sheet substrate and a ruthenium-iridium-titanium metal oxide covered thereon.
[0006] Preferably, the Ag / AgCl reference electrode is an Ag wire electrode wrapped with AgCl and having a solidified electrolyte on its surface; the head of the PTFE tube is encapsulated with a porous ceramic membrane and the tail is sealed with epoxy resin to obtain the reference electrode.
[0007] More preferably, the Ag / AgCl reference electrode is prepared by the following method: an AgCl-wrapped Ag wire electrode is placed in an uncured electrolyte in a PTFE-filled gel electrolyte, and the electrolyte is cured by ultraviolet light; the head of the PTFE tube is then encapsulated with a porous ceramic membrane, and the tail is sealed with epoxy resin to obtain a reference electrode.
[0008] Specifically, the Ag / AgCl reference electrode is prepared by the following method:
[0009] 1) Connect the Ag wire to the positive electrode of the constant voltage source, connect the standard Pt electrode to the negative electrode of the power supply, apply power to place the Ag wire and the Pt electrode in a KCl solution, and chlorinate to obtain an AgCl-wrapped Ag wire electrode;
[0010] 2) Fill the PTFE with two layers of gel electrolyte:
[0011] The first layer is: 40-60uL of [EMIM]Cl, acrylamide and 2-hydroxyethyl acrylate, 2-hydroxy-2-methylpropiophenone, and Laponite XLG aqueous solution (preferably, the mass ratio of each substance is 10-30:10-30:10-30:0.2-0.6:35-456, more preferably 20:20:20:0.4:39.6), and the electrolyte is solidified under ultraviolet light;
[0012] Add the second layer, the formula is: 100-120uL of [EMIM]Cl, acrylamide and 2-hydroxyethyl acrylate, 2-hydroxy-2-methylpropiophenone, Laponite XLG saturated KCl solution (preferably, the mass ratio of each substance is 5-15:10-30:10-30:10-30:0.2-0.6:10-306, more preferably 11:22:22:22:0.4:22.6), and cure the electrolyte under ultraviolet light;
[0013] 3) Place the AgCl-wrapped Ag wire electrode in the uncured electrolyte obtained in step 2, and irradiate it under a 365nm UV lamp for 15s to cure the second layer of electrolyte; encapsulate the head of the PTFE tube with a porous ceramic membrane and seal the tail with epoxy resin to obtain a reference electrode.
[0014] Furthermore, the specific operation of step 1) is as follows: a 0.5 mm diameter Ag wire with a purity of 99.999% is connected to the positive electrode of a constant voltage source, a standard Pt electrode is connected to the negative electrode of the power supply, the voltage is set to 3.0 V, the Ag wire and the Pt electrode are placed in a 0.1 M KCl solution, and chlorinated for 12 hours to obtain an AgCl-wrapped Ag wire electrode.
[0015] In step 2), the first and second layers are cured by using a 365nm ultraviolet lamp at an electric power of 20W to cure the electrolyte; the PTFE in step 2) has an outer diameter of 1.9mm, an inner diameter of 1.5mm, and a length of 15cm.
[0016] In a specific embodiment, the working electrode is prepared as follows:
[0017] a. Pretreatment of Ti sheet of substrate:
[0018] 1) Cut the Ti sheet into a rectangle;
[0019] 2) Polishing Ti sheet;
[0020] 3) After soaking the Ti sheet in an oxalic acid solution, the Ti sheet is dried in an oven to obtain a pretreated Ti sheet.
[0021] b. Preparation method of ruthenium iridium titanium metal oxide:
[0022] 1) First, heat citric acid and ethylene glycol in a water bath and stir thoroughly;
[0023] 2) then adding ruthenium trichloride and iridium tetrachloride into the above solution and stirring well to obtain a sol;
[0024] 3) placing the prepared sol in a vacuum oven to exhaust;
[0025] 4) The prepared sol is evenly coated on the pretreated Ti sheet, and the sheet is annealed in a furnace, and then cooled to obtain a working electrode.
[0026] Furthermore, the working electrode is prepared by the following method:
[0027] a. Pretreatment of Ti sheet of substrate:
[0028] 1) Cut a Ti sheet with a thickness of 0.04 mm and a purity of 99.99% into a rectangle of 3 mm*50 mm;
[0029] 2) Use 120-grit sandpaper to polish the titanium sheet 40 times in a single direction;
[0030] 3) The Ti was immersed in an oxalic acid solution with a mass concentration of 10% and a temperature of 60° C. for 30 minutes, rinsed with distilled water, and dried in an oven at 70° C. for 2 hours to obtain a pretreated Ti sheet.
[0031] b. Preparation method of ruthenium iridium titanium metal oxide:
[0032] 1) First, heat citric acid and ethylene glycol in a mass ratio of 1:4.25 in a 65°C water bath and stir thoroughly;
[0033] 2) then adding ruthenium trichloride and iridium tetrachloride in a mass ratio of 1:4 into the above solution and stirring well to obtain a sol;
[0034] 3) Place the prepared sol in a vacuum oven and exhaust for 30 minutes;
[0035] 4) 10uL of the prepared sol was evenly coated on the pretreated Ti sheet, and the sheet was annealed at 380°C in a furnace for 50mins. After the annealing, the sheet was placed in a 30°C oven to cool for 30mins to obtain a working electrode.
[0036] The present invention provides an application of the micro all-solid-state metal oxide pH electrode in measuring pH value, for example, for measuring the pH value of an aqueous solution sample or a fermentation liquid sample.
[0037] The present invention further provides a method for measuring pH value, which comprises the following steps:
[0038] The working electrode and the reference electrode of the micro all-solid-state metal oxide pH electrode are placed in the solution to be tested, the ends of the electrodes are connected to the WE and RE ports of the electrochemical workstation respectively using wires, and the pH in the solution is measured using the open circuit potential method.
[0039] Specifically, the solution to be tested is an aqueous solution sample or a fermentation broth sample.
[0040] The beneficial effects or advantages of the present invention compared with the prior art are: 1. The metal oxide electrode has higher mechanical strength and is not easy to be damaged; while the glass electrode will inevitably be damaged if it is accidentally dropped or touches a hard object during use; 2. The size of the working electrode base can be controlled by cutting and other means, and the size of the reference electrode can be controlled by changing the thickness of the external hard tube, so it is more convenient to miniaturize and has a wider application scenario; while the traditional glass electrode is limited by the preparation method and technology and cannot be further reduced to a smaller size, so this patent has advantages over the traditional electrode; 3. No specific transmitter is required for measurement, and the commonly used multimeter voltage measurement function can be used for measurement, which is more convenient for expansion of use; while traditional commercial electrodes cannot be measured and used unless a specific transmitter is used. This patent overcomes this monopoly and makes its application more widespread. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Comparison of cold-mode test results of pH electrodes. Among them, a) voltage change during continuous change; b) comparison of pH change between homemade pH electrode and Mettler electrode after calibration; c) pH selectivity of homemade electrode; d) comparison of time for pH to change by 95% after each addition of HCl.
[0042] Figure 2 Batch fermentation comparison between the metal oxide pH electrode of the present invention and the Mettler electrode. DETAILED DESCRIPTION
[0043] The present invention is described below through specific implementation modes in order to better understand the present invention, but it does not constitute a limitation of the present invention.
[0044] Example 1. Preparation method of metal oxide pH electrode (pH reference electrode and working electrode)
[0045] 1. Preparation of Ag / AgCl reference electrode:
[0046] 1. Connect a 0.5 mm diameter Ag wire with a purity of 99.999% to the positive electrode of a constant voltage source, and a standard Pt electrode to the negative electrode of the power supply. Set the voltage to 3.0 V, place the Ag wire and the Pt electrode in a 0.1 M KCl solution, and chlorinate for 12 hours to obtain an AgCl-wrapped Ag wire electrode.
[0047] 2. Fill two layers of gel electrolyte into the interior of PTFE with an outer diameter of 1.9 mm, an inner diameter of 1.5 mm and a length of 15 cm.
[0048] The first layer is: 20% wt. of [EMIM]Cl, acrylamide and 2-hydroxyethyl acrylate, 0.4% wt. of a mixture of 2-hydroxy-2-methylpropiophenone and Laponite XLG, and 39.6% wt. of ultrapure water; after adding 40-60uL, irradiate under a 365nm ultraviolet lamp (electric power 20W) for 15s to solidify the electrolyte;
[0049] Add the second layer, the formula is: 11% wt. of [EMIM]Cl, 22% wt. of acrylamide, 2-hydroxyethyl acrylate and 3M KCl solution, 0.4% wt. of a mixture of 2-hydroxy-2-methylpropiophenone and Laponite XLG, 22.2% wt. of ultrapure water; add a volume of 100-120uL;
[0050] 3. Place the AgCl-wrapped Ag wire electrode in the uncured electrolyte obtained in step 2, and irradiate it under a 365nm UV lamp (electric power 20W) for 15s to cure the second layer of electrolyte; the head of the PTFE tube is encapsulated with a porous ceramic membrane, and the tail is sealed with epoxy resin to obtain a reference electrode.
[0051] 2. Preparation of working electrode:
[0052] The working electrode consists of a Ti sheet substrate and a ruthenium-iridium-titanium metal oxide covering the substrate.
[0053] a. Pretreatment of Ti sheet of substrate:
[0054] 1. Cut the Ti sheet with a thickness of 0.04mm and a purity of 99.99% into a rectangle of 3mm*50mm;
[0055] 2. Use 120-grit sandpaper to polish the titanium sheet 40 times in a single direction;
[0056] 3. Soak Ti in an oxalic acid solution with a mass concentration of 10% and a temperature of 60°C for 30 minutes, rinse with distilled water, and dry in an oven at 70°C for 2 hours to obtain a pretreated Ti sheet.
[0057] b. Preparation method of ruthenium iridium titanium metal oxide:
[0058] 1. First, heat citric acid and ethylene glycol in a 65℃ water bath at a mass ratio of 1:4.25 and stir thoroughly;
[0059] 2. Then add ruthenium trichloride and iridium tetrachloride in a mass ratio of 1:4 into the above solution and stir well to obtain a sol;
[0060] 3. Place the prepared sol in a vacuum oven and exhaust for 30 minutes;
[0061] 4. Evenly apply 10uL of the prepared sol on the pretreated Ti sheet, and anneal it in a furnace at 380℃ for 50mins. After annealing, cool it in an oven at 30℃ for 30mins to obtain a working electrode.
[0062] Example 2: Experiments and results related to metal oxide pH electrodes
[0063] The following experiments are all tested using the open circuit potential method, which measures the potential across the working electrode and the reference electrode corresponding to the pH in the solution.
[0064] 1. pH electrode cold mold test
[0065] In a NaOH solution (0.1 mol / L) with an initial pH of 13, HCl solution was gradually added thereto to change the pH of the solution continuously, and the pH of the solution was measured using a Mettler electrode and the metal oxide pH electrode prepared in Example 1 and a comparative analysis was performed. The Mettler electrode was measured using its own transmitter; the reference electrode and the working electrode prepared in Example 1 were combined into a set of pH electrodes, and the open circuit potential was measured using an electrochemical workstation and converted into a pH value through a calibration curve.
[0066] The results are as follows Figure 1 As shown. Figure 1 As shown in a), as the pH decreases (pH = 12-1.6), the voltage gradually increases. In the titration stage after pH = 10, the pH changes greatly, from 10 to about 6, which is caused by the large amount of HCl added. The same is true for the next stage;
[0067] Will Figure 1 The data obtained by converting the voltage into pH in a) can be compared with the data obtained by Mettler electrode (see Figure 1 In b), the metal oxide pH electrode requires a long equilibration time of about 1000s when used for the first time; the curves of the two have a high degree of overlap in each pH change stage. In the pH stable stage, the errors are 0.95-1.45mV, corresponding to a pH error of 0.02-0.03.
[0068] Figure 1Figure c) shows the pH selectivity in the pH stable stage, which is -55mV / pH, close to the theoretical value, indicating that the electrode has good selectivity for hydrogen ions between pH = 12-1.6; in the five stages of pH change, the average time of 95% of the pH change measured by the metal oxide pH electrode is 41.2s, slightly less than the data of 37s measured by the Mettler electrode. It can be seen that the pH electrode of the present invention has a short response time, so the effect is better.
[0069] 2. pH electrode thermal model test
[0070] Experimental method for fermentation verification: During the batch fermentation culture of brewer's yeast, the use of the metal oxide pH electrode prepared in Example 1 was verified.
[0071] Batch fermentation conditions: The fermentation medium used was YPD medium (1% yeast powder, 2% glucose and 2% tryptone); a Debier bioreactor was used, and 300 mL of the medium was loaded into a 500 mL reactor;
[0072] Culture conditions: 30°C, 1000 rpm for ~24 h, inoculation volume 2%; pH changes were monitored using a Mettler pH electrode and a homemade pH electrode throughout the process;
[0073] like Figure 2 The data shown is a comparison of the metal oxide pH electrode (blue solid line) prepared in Example 1 and the Mettler electrode (red solid line) in the determination of the yeast batch fermentation process after the first sterilization. It can be found that the two have the same change trend. As the fermentation starts, the pH slowly decreases (0-10h), from 5.53 to 5.0; 10-22h pH is basically maintained near 5.0 until the end of fermentation. The metal oxide pH electrode prepared in Example 1 is consistent with the measurement data of the Mettler electrode, and the average error during the fermentation process is 0.12pH. It can be seen that the pH electrode of the present invention has achieved full solid-state electrode while maintaining a test effect basically similar to that of a traditional electrode. The advantage is that it is more convenient to miniaturize and easier to prepare than the glass structure of a traditional electrode, which has significant advantages.
Claims
1. A miniature all-solid-state metal oxide pH electrode, which consists of a reference electrode and a working electrode, characterized in that: The reference electrode is an Ag / AgCl reference electrode; the working electrode is composed of a Ti sheet substrate and a ruthenium-iridium-titanium metal oxide covered thereon.
2. The micro all-solid metal oxide pH electrode according to claim 1, characterized in that: The Ag / AgCl reference electrode is a Ag wire electrode wrapped with AgCl and having a solidified electrolyte on its surface; the head of the PTFE tube is encapsulated with a porous ceramic membrane and the tail is sealed with epoxy resin to obtain the reference electrode.
3. The micro all-solid metal oxide pH electrode according to claim 2, characterized in that: The Ag / AgCl reference electrode is prepared by the following method: placing an AgCl-wrapped Ag wire electrode in an uncured electrolyte filled with a gel electrolyte inside PTFE, curing the electrolyte by ultraviolet light; and then encapsulating the head of the PTFE tube with a porous ceramic membrane and sealing the tail with epoxy resin to obtain the reference electrode.
4. The micro all-solid metal oxide pH electrode according to claim 3, characterized in that: The Ag / AgCl reference electrode is prepared by the following method: 1) Connect the Ag wire to the positive electrode of the constant voltage source, connect the standard Pt electrode to the negative electrode of the power supply, apply power and place the Ag wire and Pt electrode in a KCl solution to obtain AgCl-wrapped Ag wire electrode by chlorination; 2) Fill the PTFE tube with two layers of gel electrolyte: The first layer is: 40-60 uL of [EMIM]Cl, acrylamide and 2-hydroxyethyl acrylate, 2-hydroxy-2-methylpropiophenone, Laponite XLG aqueous solution (preferably, the mass ratio of each substance is 10-30:10-30:10-30:0.2-0.6:35-456, more preferably 20:20:20:0.4:39.6), and the electrolyte is solidified under ultraviolet light; Add the second layer, the formula is: 100-120 uL of [EMIM]Cl, acrylamide and 2-hydroxyethyl acrylate, 2-hydroxy-2-methylpropiophenone, Laponite XLG saturated KCl solution (preferably, the mass ratio of each substance is 5-15:10-30:10-30:10-30:0.2-0.6:10-306, more preferably 11:22:22:22:0.4:22.6), and cure the electrolyte under ultraviolet light; 3) Place the AgCl-wrapped Ag wire electrode in the uncured electrolyte obtained in step 2 and irradiate it under a 365 nm UV lamp for 15 s to cure the second layer of electrolyte; encapsulate the head of the PTFE tube with a porous ceramic membrane and seal the tail with epoxy resin to obtain a reference electrode.
5. The micro all-solid metal oxide pH electrode according to claim 4, characterized in that: Step 1) Specific operation: connect a 0.5 mm diameter Ag wire with a purity of 99.999% to the positive electrode of a constant voltage source, connect a standard Pt electrode to the negative electrode of the power source, set the voltage to 3.0 V, place the Ag wire and the Pt electrode in a 0.1 M KCl solution, and chlorinate for 12 h to obtain an AgCl-wrapped Ag wire electrode; In step 2), the first and second layers are cured by irradiating with a 365 nm ultraviolet lamp at an electric power of 20 W to solidify the electrolyte; the PTFE in step 2) has an outer diameter of 1.9 mm, an inner diameter of 1.5 mm, and a length of 15 cm.
6. The micro all-solid metal oxide pH electrode according to claim 1, characterized in that: The working electrode is prepared by the following method: a. Pretreatment of Ti sheet of substrate: 1) Cut the Ti sheet into a rectangle; 2) Polishing Ti sheet; 3) Soaking the Ti sheet in an oxalic acid solution and drying it in an oven to obtain a pretreated Ti sheet; b. Preparation method of ruthenium iridium titanium metal oxide: 1) First, heat the citric acid and ethylene glycol in a water bath and stir thoroughly; 2) then adding ruthenium trichloride and iridium tetrachloride into the above solution and stirring thoroughly to obtain a sol; 3) Place the prepared sol in a vacuum oven to exhaust; 4) The prepared sol is evenly coated on the pretreated Ti sheet and annealed in a furnace. After annealing, it is cooled to obtain a working electrode.
7. The micro all-solid metal oxide pH electrode according to claim 6, characterized in that: The working electrode is prepared by the following method: a. Pretreatment of Ti sheet of substrate: 1) Cut the Ti sheet with a thickness of 0.04 mm and a purity of 99.99% into a rectangle of 3 mm*50 mm; 2) Use 120-grit sandpaper to polish the titanium sheet 40 times in a single direction; 3) Soak Ti in an oxalic acid solution with a mass concentration of 10% and a temperature of 60°C for 30 minutes, rinse with distilled water, and dry in an oven at 70°C for 2 hours to obtain a pretreated Ti sheet; b. Preparation method of ruthenium iridium titanium metal oxide: 1) First, heat citric acid and ethylene glycol in a mass ratio of 1:4.25 in a 65 ℃ water bath and stir thoroughly; 2) then adding ruthenium trichloride and iridium tetrachloride in a mass ratio of 1:4 into the above solution and stirring thoroughly to obtain a sol; 3) Place the prepared sol in a vacuum oven and exhaust for 30 mins; 4) Evenly apply 10 uL of the prepared sol on the pretreated Ti sheet, and anneal it in a furnace at 380 °C for 50 mins. After the annealing, cool it in an oven at 30 °C for 30 mins to obtain a working electrode.
8. Use of the micro all-solid-state metal oxide pH electrode according to any one of claims 1 to 7 in measuring pH value, for example, in measuring pH value of aqueous solution samples and fermentation broth samples.
9. A method for measuring pH value, characterized in that, The steps include: The working electrode and the reference electrode of the micro all-solid-state metal oxide pH electrode as claimed in any one of claims 1 to 7 are placed in the solution to be tested, the ends of the electrodes are connected to the WE and RE ports of the electrochemical workstation respectively using wires, and the pH in the solution is measured using the open circuit potential method.
10. The method according to claim 9, characterized in that The solution to be tested is an aqueous solution sample or a fermentation liquid sample.